Daya hambat rhizobakteri terhadap pertumbuhan koloni patogen terbawa benih cabai merah secara in vitro dan pengaruhnya terhadap viabilitas benih - Safriani, Safriani; Syamsuddin, Syamsuddin; Marlina, Marlina (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
The purpose of this research was to study the effect of biocontrol agents rizobakteri candidate against seed-borne pathogens colony growth in vitro of red chili and rizobakteri effect on seed germination of two varieties of chili. This research was conducted at the Laboratory of Seed Science and Technology Studies Program Faculty of Agriculture, University of Syiah Kuala. Research conducted two phases. (I) Using a completely randomized design (CRD) non factorial are 16 types rizobakteri (A. suis, Actinobacter sp, Azotobacter sp, Azotobacter sp, sp Necercia, P. capacia, B. megaterium, P. dimuta, B. bodius, B . laterophorus, B. larvae, B. alvae, Flavobacterium sp, B. coagulans, B. firmus, B. polymixa, B. lichiniformis, B. stearothermophilius) tested against pathogens (P. capsici, C. capsici, F. oxysporum , Phytium, pR. solani and S. rolfsii) by measuring the distance between the edge of the colony of pathogens and rizobakteri. (II) Using a completely randomized design (CRD) factorial design. Factors studied varieties of pepper plants (PM 999, Arena) and the type isolates rizobakteri (A. suis, Azotobacter sp, P. capacia, B. stearothermophilius, B. bodius). The benchmarks were observed maximum growth potential, percentage of germination, index of vigor, relative growth rate, simultaneity grow, and required time to reach 50% total of relative germination (T50). The test results (i) there is an effective biocontrol agent inhibits 6 types of pathogens that isolates B. bodius. Test results (II) seed treatment with rizobakteri able to improve the viability and vigor in comparison with no treatment.